Ultrasensitive Detection of 2,4-Dinitrophenol Using Nanowire Biosensor - Yuri D. Ivanov; Kristina A. Malsagova; Tatyana O. Pleshakova; Rafael A. Galiullin; Andrey F. Kozlov; Ivan D. Shumov; Irina A. Ivanova; Alexander I. Archakov; Vladimir P. Popov; Alexander V. Latyshev; Konstantin V. Rudenko; Alexander V. Glukhov (Journal of Nanotechnology)
The method for the detection of 2,4-dinitrophenol (DNP) in solution is proposed. This method employs the sensors based on silicon nanowire field-effect transistors with protective layers of high-k dielectrics, whose surface is functionalized with an amino silane. Direct highly sensitive detection of DNP has been demonstrated, and the lowest detectable concentration of DNP was determined to be 10−14 M. Silicon-on-insulator nanowire (SOI-NW) sensors can well be employed for the rapid detection of a wide range of toxic and explosive compounds by selection of sensor surface modification techniques.